Alleviation of Lower Anterior Crowding with Super-Elastic and Heat-Activated NiTi Wires: A Prospective Clinical Trial - Pasupureddi Keerthana; Prasad Chitra (Galenos Yayinevi, 2021)
Objective: To compare the amount of alleviation of lower anterior crowding and changes in intercanine width (ICW), intermolar width (IMW), and arch depth (AD) dimensions using 2 different types of nickel-titanium (NiTi) archwires.Methods: Thirty participants were randomly allocated to 2 treatment groups, using heat-activated NiTi (HANT) or super-elastic (SE-NiTi) round (0.014") archwires. The inclusion criteria were a Little's Irregularity Index (LII) greater than 4, malocclusion requiring non-extraction therapy, all teeth erupted to the second molars in the lower arch, and Angle's Class I malocclusion. The primary aim was to measure alleviation in mandibular crowding over 12 weeks; the secondary aim was to measure changes in ICW, IMW, and AD during those 12 weeks. Simple randomization was performed. The measurements were made on dental stone casts using a coordinate measuring machine at 4-week intervals.Results: LII at 0, 4, 8, and 12 weeks was 8.59 ± 1.44, 6.17 ± 1.65, 4.65 ± 1.63, and 3.28 ± 1.57 mm in the HANT; 8.87 ± 1.29, 6.92 ± 1.49, 5.25 ± 1.32, and 3.63 ± 1.32 mm in the SE-NiTi group, respectively. ICW increased from 25.43 ± 1.39 to 27.41 ± 1.29 mm in the HANT and from 25.81 ± 1.78 to 27.27 ± 1.83 mm in the SE-NiTi groups over a period of 12 weeks, at P < .05. There was a statistically significant increase in IMW, CAD (canine arch depth), and MAD (molar arch depth), favoring the HANT group (P < .05). No significant differences in LII between the 2 groups were noted (P > .05).Conclusions: The amount of alleviation of lower anterior crowding was similar with both archwires. ICW, IMW, and AD increased with HANT archwires.